Emergence of Extended Spectrum β-lactamases producing Escherichia coli among urinary tract infected patients from tertiary hospital in Nepal - Bajracharya Kishor; Bhatta Dharm Raj; Thakur Raman (BIO Web of Conferences, 2024)
Escherichia coli, a growing health concern, produces extended spectrum β-lactamases (ESBL), which are causing public health onset infections in multiple countries. Geographical variations in the distribution and prevalence of ESBL-synthesizing E. coli have been observed, with India reporting the largest proportion (61%). The worldwide dissemination of ESBL-producing bacteria, along with the restricted availability of effective treatments, could exacerbate antibiotic resistance. The identification of ESBL synthesizing E. coli is crucial for its characterisation and epidemiology in specific geographical regions. In Nepal, a developing nation, research shows a high prevalence of antibiotic-resistant bacteria, particularly the ESBL strain. Our study aimed to identify ESBL-producing E. coli from patients with urinary tract complications from a tertiary hospital in Nepal. Out of 125 E. coli isolates, 15.6% were female and 1.2% male. The highest resistance was detected for ampicillin, cefazolin, cefotaxime, and ceftazidime, while less resistance was observed against nitrofurantoin, gentamicin, and imipenem. The study found that 51 (40.8%) E. coli isolates produced ESBLs, indicating a higher level of ESBL production among urinary tract infection patients.